Facebook in qualitative research: answering ‘what’ and ‘how’ questions - Jamil, Nurul Akma; Lee, Khuan; Cheong, Ai Theng; Muda, Siti Mariam (Society of Visual Informatics, 2024)
The rapid development and widespread adoption of internet-based technology have significantly transformed the research landscape. This paper explores the potential of Facebook as a tool in qualitative research, focusing on both its applications and the challenges it presents. The main problem addressed is the complexity and ethical considerations involved in using Facebook for qualitative data collection and participant recruitment. This paper aims to analyze how Facebook can be effectively utilized while navigating these challenges. The methodology involves a detailed examination of Facebook’s features, the role of gatekeepers, and the ethical issues surrounding its use. The study also includes practical case studies where Facebook was used for qualitative research, highlighting both successes and obstacles encountered. This study suggests that although Facebook provides a valuable source of data and simplifies participant recruitment, it necessitates careful handling of privacy concerns and ethical standards. Despite the challenges, Facebook can be a powerful tool in qualitative research if used with a well-thought-out strategy. Researchers are advised to approach its use cautiously, ensuring thorough evaluation of ethical implications and practical considerations. This study contributes to the growing body of knowledge on digital research methods, providing insights and guidelines for researchers leveraging social media platforms in their work.